Lymphoid blast crisis after prolonged treatment‐free remission in chronic myeloid leukaemia after tyrosine kinase inhibitor de‐escalation during the COVID‐19 pandemic. Issue 1 (19th November 2021) - Avenoso, Daniele; Milojkovic, Dragana; Clark, James; Pocock, Christopher; Potter, Victoria; Yallop, Deborah; Hannah, Guy
Abstract: During the COVID‐19 pandemic, access to health services has been considerably restricted and furthermore, patients have been reluctant to attend for routine monitoring, and this may have had a negative impact in the management of patients affected with haematological disorders. Sudden blast crisis in chronic myeloid leukaemia is categorized as a rapid onset of blastic phase, after a documented 'optimal' response to tyrosine kinase inhibitor (TKI) therapy and within 3 months of a normal complete blood count. Herein, we describe a case of patient who developed sudden blast crisis after TKI while in treatment‐free remission.